Geostatistical Analysis and Scaling of Grapevine Root Distribution - Linsenmeier, A.W.; Löhnertz, O.; Lehnart, R. (South African Journal of Enology and Viticulture, 2011)
Geostatistical analysis was conducted for the root distribution of Vitis berlandieri x Vitis riparia using dispersion index, fractal dimension, autocorrelation and semivariance. The data were derived from the observation of roots of six 12-year old Riesling/5C vine plants in a field experiment using minirhizothron technique. The dispersion index (DI) indicated the clustering of roots. Autocorrelation as a function of the distance lag showed that a higher DI was related to higher autocorrelation at small lags. Small scale (< 3cm) spatial analysis using variograms, showed a clustering of roots at short distances (< 6cm), but also a periodicity at greater distances (16cm) with hole effects in the variograms. The spatial variance for small scale was 60-85% within a range of 5-8cm. At medium scale (5-10cm) the spatial variance decreased to 0-20%. Geostatistical analysis is a useful tool to demonstrate variation in root distribution at plant level and to improve root sampling. Although the different geostatistical tools were related, it was not possible to deduce one result from the other quantitatively.